P–359 Blastocyst quality, transfer difficulty and endometrial thickness affect clinical pregnancy after frozen embryo transfer (FET) of euploid blastocysts in the upper uterine cavity. (6th August 2021) - Bayram, A; Munck, N D; Abdala, A; Elkhatib, I; El-Damen, A; Arnanz, A; Melado, L; Fatemi, H; Lawrenz, B
Abstract: Study question: Which factors affect the clinical pregnancy rate (CPR) after single euploid frozen embryo transfers (FET), when the blastocyst is transferred in the upper uterine cavity area? Summary answer: Blastocyst quality, embryo transfer difficulty and endometrial thickness affect the CPR in FET. What is known already: There is a limited understanding of the factors affecting success rates after FET. The most important factors influencing implantation rates are patient characteristics, type of endometrial preparation, embryo quality and transfer difficulty. It has been shown that the position of the euploid blastocyst, measured as distance from the fundus (DFF) of the uterine cavity (mm), affects the implantation potential. Although the ideal location within the uterine cavity is still being debated in very heterogeneous patient populations, most studies have found that the highest pregnancy rates are obtained when the embryo is placed in the upper area of the uterine cavity. Study design, size, duration: This single center retrospective cohort study included a total of 603 single euploid FET cycles, in the upper half of the uterine cavity, between January 2019 and November 2020 in ART Fertility Clinic Abu Dhabi, UAE. Participants/materials, setting, methods: Trophectoderm biopsy samples were subjected to Next Generation Sequencing to screen the ploidy state. Vitrification and warming were performed using the Cryotop method (Kitazato, Biopharma). The full length of the uterine cavity and the longitudinal distance between the fundal endometrial surface and the air bubble after transfer were measured. Main results and the role of chance: The patients were on average 33.9 (19–46) years old. The FET was performed in a natural cycle (NC) (n = 278) or hormone replacement therapy (HRT) (n = 325). Of the 603 transfers which had been performed in the upper half of the uterus, 412 (68.3%) resulted in a pregnancy and 311 (51.5%) in a clinical pregnancy. After bivariate analysis, the clinical pregnancy rate was significantly higher for high quality blastocysts (grade 1–2 versus 3–4) (p < 0.001), after easy embryo transfers (p = 0.001) and for higher endometrial thickness (p = 0.027). After performing a multivariate logistic regression analysis to consider the effect of all explanatory variables (age, Anti Müllerian hormone, body mass index, endometrial thickness, quality of the blastocyst, difficulty of the transfer [requirement of additional instrumentation], presence of mucus or blood on the transfer catheter, day 5 or day 6 biopsy, FET endometrial preparation), the clinical pregnancy was affected by the endometrial thickness: OR 1.20 [1.05–1.37], p = 0.007; transfer difficulty: OR 0.44 [0.25–0.79], p = 0.006; blastocyst quality 3: OR 0.38 [0.18–0.79], p = 0.01 and blastocyst quality 4: OR 0.15 [0.06–0.37], p < 0.0001. Age did not affect the clinical pregnancy after transferring a single euploid blastocyst: OR 1.03 [1.00–1.06], p = 0.052. Limitations, reasons for caution: The limitation of this study was its retrospective nature and the small sample size. Other parameters may be important in live birth outcomes. Wider implications of the findings: Optimization of clinical pregnancy outcomes after FET depends on multiple factors. Even after transfer of euploid blastocysts in the upper uterine cavity, the endometrial thickness, transfer difficulty and blastocyst quality will still affect the clinical pregnancy outcomes. Trial registration number: NA